Analysis of the Role of the School Principle in Increasing the Professional Competence of SMTK Teachers in the Region of North Mollo District, South Central Timor - Baun, Soleman (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This research is to find out the role of school principals in increasing the professional competence of SMTK teachers in the North Molllo District, TTS Regency. The research used is descriptive qualitative, in this case the researcher tries to provide an overview of the Role of the Principal in Improving Professional Competence. The data analysis technique used is narrative descriptive which is applied with three paths, namely data reduction, data presentation and conclusion/verification. Based on the results of the research, it can be concluded that: 1) The professional competence of regional SMTK teachers in North Mollo District is quite good. In terms of the competence of educators can be said to be professional. Some SMTK teachers have implemented learning methods in accordance with the applicable curriculum, and also used various variations of learning methods with the aim that students are not bored with the ongoing lessons.